Особливості професійного вибору в галузі “Фізичне виховання і спорт” - Степанченко, Наталія (Видавництво Львівської політехніки, 2013)
Рассматриваются особенности мотивации выбора профессии тренера-преподавателя в области “Физическое воспитание и спорт”. Представлены результаты лонгитюдных исследований спортивной квалификации абитуриентов, самооценки педагогических возможностей и результаты степени информированности абитуриентов об условиях работы специалистов по физической культуре и спорту. The article deals with the peculiarities of choice motivation of the trainer-teachers’ profession in the sphere of “Physical Education and Sport”. The author presents the results of longitude researches concerning sport qualification of applicants, self-evaluation of pedagogical possibilities and the results of the level of their awareness about work conditions of physical culture and sports specialists.
Особенности профессионального выбора в сфере “Физическое воспитание и спорт”
Particularities of professional choice in the sphere of “physical education and sport”
Keywords: физическое воспитание и спорт; абитуриент; профессиональный выбор; особенности мотивации; physical education and sport; applicants; professional choice; motivation particularities